The orphan's tale - Jenoff, Pam (ill., 2017)
Sixteen-year-old Noa, forced to give up her baby fathered by a Nazi soldier, snatches a child from a boxcar containing Jewish infants bound for a concentration camp and takes refuge with a traveling circus, where Astrid, a Jewish aerialist, becomes her mentor